The Influence of Social Media Marketing and Brand Image on Intention to Purchase Residential Apartments - Tarigan, Arihta; Noverin, Devina Tasya (Jurnal Ilmiah Manajemen dan Bisnis, 2024)
The rising attraction towards the real estate sector in the Jabodetabek region, particularly apartments due to land limitations, has prompted developers to adopt social media platforms for marketing their offerings. A notable player, PT PP Properti Tbk, employs Instagram as a tool for showcasing its products. This study’s objective is to assess how social media marketing and brand image impact the inclination to buy residential apartment products by PT PP Properti Tbk. This research is a descriptive quantitative investigation that establishes and elucidates links between variables. It focuses on individual variables without drawing parallels or associations with others. The sampling technique comprises a questionnaire, distributed to 122 respondents. These respondents are consumers who have follow and engaged with call-to-action (CTA) on the Instagram account @ppproperti. Data analysis was facilitated through SPSS 26 software, encompassing validity, reliability, and hypothesis testing. The research findings highlight that both social media marketing and brand image, collectively and individually, wield a favourable influence on the purchase intention for residential apartment products under PT PP Properti Tbk. These findings offer valuable insights for refining strategies in Instagram-based social media marketing and brand image, aimed at nurturing purchase intention. Furthermore, PT PP Properti Tbk can implement these research outcomes to heighten consumer interest in their residential apartment products in the times ahead.